Risk and genetic susceptibility to arsenic exposure from drinking groundwater in populations of the Colombian Caribbean (2020)
Inorganic arsenic (InAs) is considered to be the principal form of arsenic (As) in groundwater. The presence of arsenic in waters naturally may occur and it is a serious global health issue, playing a very important role in the chronic toxicological effect in humans. According to International Agency for Research on Cancer (IARC), InAs species are classified in Group I as “carcinogens to human”. World Health Organization (WHO) had recommended a guideline value for arsenic in drinking water as a safe of 10 μg/L. Before starting this project, there was very little information on As concentrations in groundwater in Colombia. On the other hand, this research provided for the first time on two publications of international impact on As exposure in humans and the magnitude of the problem that had been completely unknown in Colombia. Lifetime average daily dose (LADD) is considered an important method for exposure assessment, because the effects of toxicity of InAs may be accelerated with an increase in exposure dosage. Knowledge of the mechanism of environmental exposure to As will allow the understanding of the individual differences to identify susceptible groups. Urinary arsenic species such as trivalent arsenic (AsIII), pentavalent arsenic (AsV ), mono-methyl arsenic acid (MMA) and dimethyl arsenic acid (DMA) have been used as biomarkers for the LADD of arsenic. However, this profile's urinary of speciation can vary largely among individuals. This can be due to demographic, anthropometric factors such as age, sex, body mass index (BMI) and pregnancy, as well as smoking history and lifestyle. Besides, genetic factors have been reported to explain part of the variation and probably plays an important role in the arsenic methylation, increasing the susceptibility to arsenic exposure. Nevertheless, more consistent evidence is needed on the focus of this issue, which contributes explanations according to the effect of the interactions among different polymorphic variants and other potential factors involved on the metabolic process of As. The aim of this study was to evaluate the risk of arsenic exposure in humans and the effects of genetic variants on urinary arsenic profiles in people exposed from drinking groundwater of the Department of Bolivar, Colombia. For this purpose, specific surveys were used to assess the demographic and anthropometric information of the subjects and their lifestyle. The groundwater samples were analyzed for assessing total arsenic (TAs) and speciation (AsIII and AsV ) using highperformance liquid chromatography, with hydride generation (HG), couple to atomic fluorescence spectrometry (HPLC-HG-AFS). Likewise, the exposure and risk of arsenic was assessed by LADD method (µg/kg bw/day) and the Hazard quotient (HQ). Besides, urinary arsenic metabolites: AsIII, AsV , MMAV , and DMAV were measured using HPLC-HG-AFS. Six genetic polymorphisms (GSTO2-rs156697, GSTP1-rs1695, GSTT1, GSTM1, As3MT-rs3740400 and MT2Ars28366003) were evaluated from DNA samples by real-time and/or conventional PCR. Twenty-two groundwater wells from studied municipalities were analyzed. The high exposure of As (0.33 µg/kg bw/day) in the study population generated a risk of adverse health effects HQ=1.2. The urinary arsenic species concentrations were 0.80 µg/L for InAs, 0.60 µg/L for MMAV and 1.2 µg/L for DMAV . The associated between urinary arsenic species and genetic polymorphisms showed MMA urinary excretion higher in subjects with heterozygous and/or homozygous genotypes of As3MT. Furthermore, DMA and ratio MMA/InAs were lower in individuals with heterozygous and/or homozygous genotypes of GSTP1. Likewise, DMA and MMA concentrations were higher in GSTM1-null genotypes. For GSTT1 and MT2A genotypes no differences were found. Interactions gene-gene and gene-covariates modified the MMA and DMA urinary excretion. In conclusion, the interactions between As3MT*GSTM1 y GSTO2*GSTP1 polymorphic variants could be potential modifiers of the risk of toxicity to inorganic arsenic through an increase of MMA and InAs a decrease of DMA and primary methylation index (PMI ratio). The synergistic effect among these polymorphisms and age, daily doses of arsenic, and alcohol consumption might vary the arsenic individual metabolic capacity a large part.